Sleep Quality and Depression Level in Nurses in COVID-19 Pandemic - Tosun, Ayşe; Tosun, Hale; Özkaya, Birgül Ödül; Erdoğan, Zeynep; GÜL, ASİYE (Sage Publications Inc., 2022)
The COVID-19 spread rapidly all over the world and pandemic process has negatively affected nurses. Sleep disorders and depression are among these negative effects. Managers' awareness of problems experienced by nurses and taking precautions will increase employee and patient satisfaction and provide quality patient care. The study was conducted in descriptive, cross-sectional and correlational design to explain nurses' sleep quality and depression levels and relationship between them during the COVID-19 pandemic with 142 nurses who completed Personel Information Form, Pittsburgh Sleep Quality Index (PSQI) and Beck Depression Index (BDI). Sleep quality of nurses (64.8%) was poor, 33.1% had depression, and high school education, having a chronic illness and PSQI score increased the risk of depression level of nurses. Results highlight COVID-19 pandemic affected nurses' sleep quality and depression levels. All managers should be pioneers in providing psychological support to nurses and preparing and implementing a program for prevention of insomnia and depression.
Keywords: Covid-19; Depression Level; Nursing; Sleep Quality; Work Condition